Foreign Body Granulomas Induced by Intramuscular Leuprorelin Acetate Injection for Prostate Cancer: Clinical Mimics of Soft Tissue Sarcoma. (31st March 2015) - Thway, Khin; Strauss, Dirk C.; Smith, Myles J.; Fisher, Cyril
Abstract : We describe two cases of florid, foreign body granulomatous reaction occurring in the upper arms of males in their eighth decade, who were undergoing treatment with depot injection of leuprorelin acetate for prostatic carcinoma. These patients presented with rapidly enlarging extremity soft tissue masses and were referred to a tertiary sarcoma center with clinical suspicion of a primary soft tissue neoplasm. The occurrence of injection site granulomas secondary to leuprorelin acetate administration is rarely known outside the urological and dermatological communities, and their recognition is important due to the spectrum of clinical differential diagnoses and potential for diagnostic confusion with metastatic prostatic cancer and primary sarcoma and in order to avoid unnecessary stress and clinical intervention for patients.